Design, synthesis, and in vitro evaluation of aza-peptide aldehydes and ketones as novel and selective protease inhibitors. (1st January 2020) - Corrigan, Thomas S.; Lotti Diaz, Leilani M.; Border, Sarah E.; Ratigan, Steven C.; Kasper, Kayla Q.; Sojka, Daniel; Fajtova, Pavla; Caffrey, Conor R.; Salvesen, Guy S.; McElroy, Craig A.; Hadad, Christopher M.; Doğan Ekici, Özlem
Abstract: Aza-peptide aldehydes and ketones are a new class of reversible protease inhibitors that are specific for the proteasome and clan CD cysteine proteases. We designed and synthesised aza-Leu derivatives that were specific for the chymotrypsin-like active site of the proteasome, aza-Asp derivatives that were effective inhibitors of caspases-3 and -6, and aza-Asn derivatives that inhibited S. mansoni and I. ricinus legumains. The crystal structure of caspase-3 in complex with our caspase-specific aza-peptide methyl ketone inhibitor with an aza-Asp residue at P1 revealed a covalent linkage between the inhibitor carbonyl carbon and the active site cysteinyl sulphur. Aza-peptide aldehydes and ketones showed no cross-reactivity towards cathepsin B or chymotrypsin. The initial in vitro selectivity of these inhibitors makes them suitable candidates for further development into therapeutic agents to potentially treat multiple myeloma, neurodegenerative diseases, and parasitic infections.